2013
DOI: 10.1089/bsp.2013.0053
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Laboratory Evaluation of a Highly Specific Lateral Flow Assay for the Presumptive Identification of Ricin in Suspicious White Powders and Environmental Samples

Abstract: Ricin, a heterodimeric toxin that is present in the seeds of the Ricinus communis plant, is the biothreat agent most frequently encountered by law enforcement agencies in the United States. Even in untrained hands, the easily obtainable seeds can yield a highly toxic product that has been used in various types of threats, including "white-powder" letters. Although the vast majority of these threats are hoaxes, an impediment to accurate hazard assessments by first responders is the unreliability of rapid detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…None of the immunoassay product's claimed limits of detection were achieved with our spore testing, although our ricin immunoassay results were comparable to other published studies. 19,21 As demonstrated by our preliminary studies on B. anthracis growth media and strain type, the differences between PNNL B. anthracis limit of detection estimates, manufacturer claims, and published data could be due to variations in sample preparation or spore strain type. For products that had optional optical readers, we found that the use of an optical reader does not always improve sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…None of the immunoassay product's claimed limits of detection were achieved with our spore testing, although our ricin immunoassay results were comparable to other published studies. 19,21 As demonstrated by our preliminary studies on B. anthracis growth media and strain type, the differences between PNNL B. anthracis limit of detection estimates, manufacturer claims, and published data could be due to variations in sample preparation or spore strain type. For products that had optional optical readers, we found that the use of an optical reader does not always improve sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…48 Simple to use and requiring minimal training, 49 LFAs are ideal for use by first responders and law enforcement officers to test suspicious materials in field settings. BioThreat Alert Ò Assays have previously been evaluated for the detection of other biothreat agents, including orthopoxviruses, 50 ricin, 33 abrin, 34 and Yersinia pestis. 51 Limited evaluations have also been conducted with LFAs for the detection of Francisella tularensis (unpublished data), botulinum neurotoxins, 52 and staphylococcal enterotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Während mit Labormethoden beispielsweise Toxine im ein-bis zweistelligen Picogramm-pro-Milliliter-Bereich nachgewiesen werden können [19], sind kommerzielle Lateral Flow Assays (LFA) um einen Faktor 1000 weniger empfindlich und benötigen bestenfalls wenige Nanogramm pro Milliliter für den Toxinnachweis [20]. Der Hauptgrund hierfür liegt im direkten Nachweis der Antikör-perbindung, wohingegen bei Labormethoden enzymatische Signalamplifikationsschritte zu einer deutlichen Steigerung der Sensitivität führen [21].…”
Section: Immunologische Schnelldetektionsverfahrenunclassified